Wish upon a sleepover! ebook - Nickelodeon Publishing (Shimmer and Shine., 2016)
Shimmer and Shine make their first sleepover a night to remember! Girls and boys ages 2 to 5 will love this love this all-new storybook starring Nickelodeon's silliest genies. This Nickelodeon read-along contains audio narration.